PEMBERDAYAAN MASYARAKAT MELALUI PENERAPAN BUDIDAYA IKAN HIAS AIR TAWAR DI KARANG TARUNA SINGO JOYO KABUPATEN MALANG - Ganjar Adhywirawan Sutarjo; Hany Handajani (Jurnal Abdi Insani, 2023)
Increasing the potential of the local economy can be done through the involvement of productive age communities, namely youth who are members of the youth organization. Karang Taruna is a social organization as a forum and means of development for every member of the community, growing based on social awareness and responsibility from, for and on behalf of the community, especially the village or sub-district youth generation. A youth organization that is part of the youth group "Singo Joyo" in Jedong Village, Wagir District, Malang Regency. One of the activities carried out by the youth organization "Singo Joyo" is the cultivation of ornamental fish Channa sp. or better known as ornamental cork fish, and betta fish. The purpose of this activity is to increase the knowledge and skills of the "Singo Joyo" youth group regarding the application of management of freshwater ornamental fish farming, the application of natural feed production techniques (Daphnia sp., and silk worms) as the main natural food for freshwater ornamental fish larvae, and implementation of water quality management based on recirculation systems. The method for implementing this internal community service program (PPMI) is carried out using a training and mentoring method approach related to the implementation of freshwater ornamental fish farming management and water quality management. The results of PPMI activities are increasing the knowledge and skills of the "Singo Joyo" youth group partners in implementing good management of freshwater ornamental fish farming, partners are able to increase the percentage of production to 60% from before the activity which was 30%. The conclusion from this activity is that partners are able to implement freshwater ornamental fish production management so that production capacity increases by up to 60%.